2021
DOI: 10.1016/j.mehy.2020.110365
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell vaccine immunotherapy; the beginning of the end of cancer and COVID-19. A hypothesis

Abstract: Immunotherapy is the newest approach to combat cancer. It can be achieved using several strategies, among which is the dendritic cell (DC) vaccine therapy. Several clinical trials are ongoing using DC vaccine therapy either as a sole agent or in combination with other interventions to tackle different types of cancer. Immunotherapy can offer a potential treatment to coronavirus disease 2019 (COVID-19) the worst pandemic facing this generation, a disease with deleterious effects on the health and economic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
2
19
0
3
Order By: Relevance
“…This is consistent with the reduction of lymphocytes as one of the clinical characteristics of COVID-19 [19]. In addition, we understand that DC vaccine therapy can be used to combat the COVID-19 epidemic and to overcome the possibility of re-infection of the virus [20]. At the same time, in our study of correlations between FURIN and several immune characteristics, we found that most marker genes in immune in ltration cells were also associated with highly expressed FURIN.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the reduction of lymphocytes as one of the clinical characteristics of COVID-19 [19]. In addition, we understand that DC vaccine therapy can be used to combat the COVID-19 epidemic and to overcome the possibility of re-infection of the virus [20]. At the same time, in our study of correlations between FURIN and several immune characteristics, we found that most marker genes in immune in ltration cells were also associated with highly expressed FURIN.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the reduction of lymphocytes as one of the clinical characteristics of COVID-19 [ 28 ]. In addition, we understand that DC vaccine therapy can be used to combat the COVID-19 epidemic and to overcome the possibility of re-infection of the virus [ 29 ]. At the same time, in our study of correlations between FURIN and several immune characteristics, we found that most marker genes in immune infiltration cells were also associated with highly expressed FURIN.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess trans infection of targeted T cells, C-SIGN is important, despite not being a receptor in SARS-CoV infection. Antibodies raised against DC-SIGN can inhibit DC infections and become targets for designing new therapies [72]. It is now well known that pulmonary pneumocytes are the most extensive lung cell infected with SARS-CoV-2.…”
Section: Immunotherapy and Vaccinementioning
confidence: 99%